Temporal trends in incidence of atrial fibrillation in primary care records: a population-based cohort study. Issue 12 (23rd December 2020) - Mendonça, Sílvia C; Saunders, Catherine L; Lund, Jenny; Mant, Jonathan; Edwards, Duncan
Abstract : Objectives: Atrial fibrillation (AF) is a heart condition associated with a fivefold increased risk of stroke. The condition can be detected in primary care and treatment can greatly reduce the risk of stroke. In recent years, a number of policy initiatives have tried to improve diagnosis and treatment of AF, including local National Health Service schemes and the Quality and Outcomes Framework. We aimed to examine trends in the incidence of recorded AF in primary care records from English practices between 2004 and 2018. Design: Longitudinal cohort study. Setting: English primary care electronic health records linked to Index of Multiple Deprivation data. Participants: Cohort of 3.5 million patients over 40 years old registered in general practices in England, contributing 22 million person-years of observation between 2004 and 2018. Primary and secondary outcome measures: Incident AF was identified through newly recorded AF codes in the patients' records. Yearly incidence rates were stratified by gender, age group and a measure of deprivation. Results: Incidence rates were stable before 2010 and then rose and peaked in 2015 at 5.07 (95% CI 4.94 to 5.20) cases per 1000 person-years. Incidence was higher in males (4.95 (95% CI 4.91 to 4.99) cases per 1000 person-years vs 4.12 (95% CI 4.08 to 4.16) in females) and rises markedly with age (0.58 (95% CI 0.56 to 0.59) cases per 1000 person-years in 40–54 years old vs 21.7 (95% CI 21.4 to 22.0) cases in over 85s). The increase in incidence over time was observed mainly in people over the age of 75, particularly men. There was no evidence that temporal trends in incidence were associated with deprivation. Conclusions: Changes in clinical practice and policy initiatives since 2004 have been associated with increased rates of diagnosis of AF up until 2015, but rates declined from 2015 to 2018.